Reading assessment : linking language, literacy, and cognition - Farrall, Melissa Lee. (Hoboken, New Jersey : John Wiley and Sons, Inc., 2012)
'This accessible, friendly guide is the first of its kind to present a research-based, integrated review of reading, cognition, and oral language testing and assessment. The theoretical underpinnings of reading, language, and literacy are covered, as well as detailed information and administration tips on the myriad reading inventories that may be used in a reading psychoeducational assessment. Unique in its inclusion of instruction on crafting professional evaluation reports to illuminate a student's strengths and weaknesses, this inviting book will enable school psychologists, reading specialists, and learning disabilities specialists to conduct effective interdisciplinary remedial recommendations and interventions'--
FrontMatter -- Introduction -- Reading Theory and Stages of Reading Acquisition -- Oral Language -- Linguistic and Cultural Diversity -- Statistics and Test Development -- Test Administration and Report Writing -- Response to Intervention -- Role of Intellectual Assessment -- Oral Language Assessment -- Underlying Processes -- Decoding -- Comprehension -- Informal Inventories and Readability -- Written Expression and Spelling -- Last Words -- Appendix A: Answer Key -- Appendix B: Glossary -- References -- Additional Resources -- Author Index -- Subject Index.
Machine generated contents note: Acknowledgments Chapter 1: Introduction Chapter 2: Reading Theory and the Stages of Reading Acquisition Chapter 3: Oral Language Chapter 4: Linguistic and Cultural Diversity Chapter 5: Statistics and Test Development Chapter 6: Test Administration and Report Writing Chapter 7: Response to Intervention Chapter 8: The Role of Intellectual Assessment Chapter 9: Oral Language Assessment Chapter 10: Underlying Processes Chapter 11: Decoding and Fluency Chapter 12: Comprehension Chapter 13: Informal Inventories and Readability Chapter 14: Written Expression and Spelling Chapter 15: Last Words Appendix A: Answer Key Appendix B: Glossary References Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Reading -- Ability testing; Educational tests and measurements; Reading, Psychology of; Cognition in children; PSYCHOLOGY -- Education & Training; Cognition in children; Educational tests and measurements; Reading -- Ability testing; Reading, Psychology of; PSYCHOLOGY -- Education & Training; Electronic books; Electronic books